Stable and reproducible expression of bacterial ipt gene under the control of SAM-specific promoter (pKNOX1) with interference of developmental patterns in transgenic Peperomia pellucida plants - Worakan, Phapawee; Gujjar, Ranjit Singh; Supaibulwatana, Kanyaratt (Frontiers in Plant Science, 2022)
Reproducible and stable transgene expression is an important goal in plant basic research and applications. Hence, we report the first stable expression of bacterial transgenes in medicinal plant, Peperomia pellucida (L.) Kunth. Two key elements relevant to the dynamic expression of the bacterial cytokinin biosynthesis gene, ipt (isopentenyltransferase) were examined. First, by designing a specific expression cassette driven by a tissue-specific promoter for the required levels of gene expression in the particular function of development, and second by using P. pellucida as a model plant due to its short developmental cycle that supported expedient tracking of transgene expression in the progeny. Transgenic frequencies of ipt gene obtained from different expression cassettes of pKNOX1 for tissue-specific promoter in shoot apical meristem were compared with the cauliflower mosaic virus (CaMV35S) promoter (p35S), a constitutive promoter investigated for T3 generation. It was clearly shown that transgenic plants with pKNOX1 showed percentage of survivals in T3 at about 2.2 folds more than those of p35S-transgenic. Transgenic P. pellucida under controllable expression of pKNOX1 showed increased leaf and seed size with a high percentage of fertile seed, whereas transgenic plants with p35S showed phenotypic features of bushy and small leaves, sterile pollen and lower reproductive fitness. Quantitative examination of ipt-positive gene expression in T3 generation of transformants with pKNOX1 were 100% (line k-14) and 50% (line k-20), while 33.3% was observed in transgenic line c-11 with p35S. Interestingly, the endogenous cytokinin biosynthesis gene (ipt3) was significantly upregulated (2-3 folds higher) in pKNOX1-transformants. The overall relative mRNA expression of bacterial ipt gene and overproducing of cytokinin contents (t-ZR and 2-iP) detected in p35S-transformants caused abnormality and low percentages of transgene reproducible Interestingly, pKNOX1-transgenic plants tended to maintain chlorophyll contents 4-5 folds and extending the developmental cycle to 12.4 weeks (wk), which was 2 folds more than wildtype (5.8 wk) and p35S-transformants (7.4 wk). The promotor effect on stable and reproducible transgene-expressions demonstrated prominent features of P. pellucida and also empowered further omics studies.